Field-tuned superconductor–insulator transitions and Hall resistance in thin polycrystalline MoN films. (17th January 2018) - Makise, Kazumasa; Ichikawa, Fusao; Asano, Takayuki; Shinozaki, Bunju
Abstract: We report on the superconductor–insulator transitions (SITs) of disordered molybdenum nitride (MoN) thin films on (1 0 0) MgO substrates as a function of the film thickness and magnetic fields. The T c of the superconducting MoN films, which exhibit a sharp superconducting transition, monotonically decreases as the normal state R sq increases with a decreasing film thickness. For several films with different thicknesses, we estimate the critical field H c and the product zν ≃ 0.6 of the dynamical exponent z and the correlation length exponent ν using a finite scaling analysis. The value of this product can be explained by the (2 + 1) XY model. We found that the Hall resistance Δ R xy ( H ) is maximized when the magnetic field satisfies H HP ( T ) ∝ |1 − T / T C0 | in the superconducting state and also in the normal states owning to the superconducting fluctuation corresponding to the ghost critical magnetic field. We measured the Hall conductivity δσ xy ( H ) = σ xy ( H ) − σ x y n and fit the Gaussian approximation theory for δσ xy ( H ) to the experimental data. Agreement between the data and the theory beyond H c suggests the survival of the Cooper pair in the insulating region of the SIT.